PENGARUH REKRUTMEN DAN PENEMPATAN TERHADAP KINERJA KARYAWAN PT. TAINAN ENTERPRISES INDONESIA 3 - Novel Supriyanti; Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
This study aims to determine the effect of recruitment, job placement on the performance of employees of PT. Tainan Enterpises Indonesia 3. The data analysis with validity and reliability testing, classical assumption test, and hypothesis testing using simple and multiple linear regression analysis. The results showed that partially recruitment had no effect on employee performance , while job placement had an effect on employee performance at PT. Tainan Enterprises Indonesia 3. Simultaneously recruitment and job placement affect employee performance at PT. Tainan Enterprises Indonesia 3.